KESALAHAN PENGGUNAAN IMBUHAN DALAM KARANGAN DESKRIPSI SISWA KELAS VII. 11 SMP NEGERI 3 MAKASSAR: ERRORS IN THE USE OF AFFIXES IN DESCRIPTION ESSAYS OF STUDENTS IN CLASS VII. 11 SMP NEGERI 3 MAKASSAR - Halim, Yuliana; Hamsa, Akmal; Agussalim AJ, Andi (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research aims to describe prefix, suffix, simulfix and confix errors in students' description essays. This research method uses qualitative research method. The data source in this research is students' description essays. The research instrument used is the researcher who uses data cards. The data analysis technique in this study is that the researcher reads, observes, and marks the data in the students' description essays that have been collected. While the data collection techniques are documentation and observation. Based on the results of analysis and discussion in the description essays of students of class VII.11 SMP Negeri 3 Makassar, prefix errors were found as much as 20 data, suffix errors were found as much as 3 data, simulfix errors were found 1 data, and confix errors were found as much as 3 data